Study of Flood-Prone Areas in Bekasi Regency - Agustina, Ina Helena (Indonesia University of Education, 2021)
Bekasi Regency is a potential area economically because there is the largest industrial area in Southeast Asia. However, Bekasi experiences the threat of flooding every year. The growth of the Bekasi Regency area has been affected by the growth of the Jakarta area, even becoming part of the JABODETABEK Metropolitan area (Jakarta-Bogor-Depok-Tangerang-Bekasi. This shows a potential location for economic growth in Bekasi Regency. Bekasi Regency is a West Java Province Region and is hydrologically included in the Regional Unit River (SWS) from the Citarum River Basin. The purpose of this study is to describe flood-prone areas in Bekasi Regency. The research method uses data collection methods by means of surveys and field observations. The data obtained are primary and secondary data, analyzed using ARCH GIS assistance to map flood-prone areas and their inundation and drainage channel conditions. The study findings will provide lessons on flood cases in Bekasi Regency. Flood cases that can provide knowledge related to cases of coastal areas and cases of areas that have high economic potential.